Efficacy of intralesional immunotherapy for the treatment of warts: A review of the literature. Issue 3 (15th March 2016) - Aldahan, Adam Souhail; Mlacker, Stephanie; Shah, Vidhi V.; Kamath, Preetha; Alsaidan, Mohammed; Samarkandy, Sahal; Nouri, Keyvan
ABSTRACT: Warts are common epidermal growths caused by human papillomavirus that often cause significant discomfort and embarrassment. Current treatment options include topical therapies, cryotherapy, laser vaporization, and surgical excision. Many of these options are destructive and may result in scarring, while less aggressive approaches can lead to lesion recurrence. Additionally, these local modalities are not practical for patients with a large number of warts. Systemic approaches such as immunotherapy have demonstrated success in treating multiple lesions by combining a targeted approach with upregulation of the host immune system. An extensive literature review was performed to evaluate the various vaccine antigens that have been used intralesionally to treat cutaneous and anogenital warts. The specific intralesional immunotherapies that have been studied include: Candida albicans ; measles, mumps, and rubella; Trichophyton ; and tuberculin antigens such as purified protein derivative, Mycobacterium w vaccine, and Bacillus Calmette‐Guerin. Intralesional vaccine injection represents a safe, effective, and tolerable treatment for warts, including recalcitrant and anogenital warts. This approach has been somewhat overlooked in the past despite substantial evidence of high response rates with a low side effect profile. Large comparative trials are necessary to determine the most effective immunotherapy treatment option as well as the most appropriate dosing parameters.